2023
DOI: 10.1099/mgen.0.001020
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of Staphylococcus aureus isolated from bloodstream infections in South America during 2019 supports regional surveillance

Abstract: Staphylococcus aureus remains one of the leading causes of infections worldwide and a common cause of bacteraemia. However, studies documenting the epidemiology of S. aureus in South America using genomics are scarce. We hereby report on the largest genomic epidemiology study to date of both methicillin-resistant S. aureus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…However, the hVISA strain recovered in this research, corresponding to ST30, exhibited similar microbiological characteristics to an hVISA strain isolated from a neonate's blood culture in Brazil in 2009 [10]. The ST30 (CC30) has been circulating in the region and Uruguay since the beginning of the burden of community-acquired MRSA (CA-MRSA) infections and remains present today [12][13][14]. Therefore, considering the proposed mechanisms for hVISA emergence, it is plausible that this specific ST had been exposed to vancomycin for an extended period, especially given the documented increase in vancomycin use in this hospital since the 2002 CA-MRSA outbreak in Uruguay [5,8].…”
Section: Discussionmentioning
confidence: 64%
“…However, the hVISA strain recovered in this research, corresponding to ST30, exhibited similar microbiological characteristics to an hVISA strain isolated from a neonate's blood culture in Brazil in 2009 [10]. The ST30 (CC30) has been circulating in the region and Uruguay since the beginning of the burden of community-acquired MRSA (CA-MRSA) infections and remains present today [12][13][14]. Therefore, considering the proposed mechanisms for hVISA emergence, it is plausible that this specific ST had been exposed to vancomycin for an extended period, especially given the documented increase in vancomycin use in this hospital since the 2002 CA-MRSA outbreak in Uruguay [5,8].…”
Section: Discussionmentioning
confidence: 64%
“…In large-scale population genomic studies from other parts of the world, CC5 and CC8 are also prevalent in MRSA from bloodstream infections, but other lineages are also major contributors. In a study from Argentina, Bolivia, Brazil, Paraguay, and Uruguay, CC5, CC8, and CC30 were common in 2019 38 . Lineages CC5, CC8, and CC22 were dominant in Spain from 1990 to 2019 39 .…”
Section: Discussionmentioning
confidence: 98%
“…Initially being reported in North America in the early 2000s ( Enright et al, 2002 ), ST59 MRSA has gradually been replacing ST239 and ST5 human clones and become the predominant sequence type in most hospitals of China since 2010 ( Li et al, 2018 ; Jin et al, 2021 ; Wang et al, 2022 ). However, ST59 MRSA remains geographically confined and is low prevalence in Europe and North America ( Pimentel de Araujo et al, 2021 ; Di Gregorio et al, 2023 ). Previous studies have shown ST9 is the dominant LA-MRSA in China and other Asian countries as opposed to ST398 in Europe and North America ( Silva et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%